MSP: An emerging player in metabolic syndrome. Issue 1 (February 2015) - Li, Jieyi; Chanda, Dipanjan; Shiri-Sverdlov, Ronit; Neumann, Dietbert
Highlights MSP is a key negative regulator in inflammation in multiple disease models. MSP has potential beneficial effects in regulation of lipid and glucose metabolism. MSP may possibly act as a crucial regulator of metabolic syndrome.